To tell or not to tell … the patient about potential harm - Bartholow, Timothy L. (Frontiers in Nuclear Medicine, 2023)
Extravasation, as distinct from infiltration, is when a potentially toxic agent (e.g., radiographic contrast, chemotherapy, anesthesia or radionuclide) is unintentionally administered to the surrounding tissue instead of directly into the vein. There is an expectation for vascular access in interventional medicine across nearly all specialties that this high frequency, study/treatment critical procedure needs to occur with rare failure and that this failure rate should be characterized in quality assurance. This opinion piece, written by a family practitioner who has served as the chief medical officer for a not-for-profit payer, reflects on our responsibility to be aware as clinicians of known potential harm and disclose to patients before a risk occurs and if harm has occurred. In this paper, clinical obligations of reporting will be reviewed, which are necessary to maintain and enhance our trust with our patients. In the second half, the perspectives of a not-for-profit payer chief medical officer will be considered.